(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
A sorption-photometric test method for preconcentration and determination of mercury (II) was developed using silica gel modified with 1,2-naphthoquinone thiosemicarbazone. Modification of silica gel with a reagent was carried out from the chloroform-hexane solution for 3 hours. Pocket photometer was used for the measurement of reflected (transmitted) light from silica modified after sorption of thiosemicarbazonate of Hg(II). The adsorption capacity of the sorbent has been found to be 35 µmol g-1 for 1,2-naphthoquinone thiosemicarbazone. The effects of pH, sorption time, the volume of aqueous solution were studied. In the optimal conditions (pH 3.0; 5 min; 25°C) the extraction recovery of mercury is 90–95%. The range of concentrations of mercury (ІІ) is 50–600 мg L–1, the detection limit (S/N = 3) is 23 мg L–1. The method is tested in the model tap and natural water samples, relative standard deviation for 50 µg L−1 of Hg(II) is below 9.0 % (n = 3). The interference effect of the most common heavy metals in natural water, as Fe (III), Zn (II) and Mn (II) ions were studied. The EDTA solution was added for the binding of these metals, which forms strong colorless complexes with EDTA. We have shown that in the presence of 0,01 M EDTA solution Fe (III), Zn (II) and Mn (II) ions, each up to 500 µg L−1, do not interfere with the determination of mercury (II) at its content of 50 µg L−1. The method can be used for the determination of mercury in the sewage of various industries and natural waters with its high content. The proposed method is inexpensive, simple, fast, and environmentally friendly for the determination of the micro quantities of mercury (II) in the water samples.